Effectiveness of DOTS regime in terms of cure, failure, default and relapse in the treatment of TB patients - K., Jahnavi; Sreenivasulu, T. (International Journal of Advances in Medicine, 2018)
Background: DOTS has given very good results in terms of cure and satisfaction among tuberculosis patients. But still some failure and relapse cases occur. Hence studies on effectiveness of DOTS are required. The objectives of research were to study the effectiveness of DOTS regime in terms of cure, failure, default and relapse in the treatment of TB patients Methods: A hospital based prospective follow up observational study was undertaken in the department of general medicine at a tertiary care medical college and hospital. The present study was conducted among the 60 eligible subjects as per the inclusion and exclusion criteria laid down for the present study. Results: 41 were pulmonary cases and 19 were extra pulmonary patients. At the end of intensive phase only 7 cases were sputum positive out of 37 which reduced to three at the end of extended intensive phase of treatment which further reduced to two at the end of two months of continuation phase. But by the end of completion of continuation phase, one case again became sputum positive i.e. failure case making a final tally to three. It was seen that there was significant weight gain over the period of time in both pulmonary and extra pulmonary cases. The cure rate was 78%. One patient died. Two defaulted and three were failure cases. Conclusions: The DOTS was found to be 78% effective in terms of cure rate. Still there is a huge gap of 22% found in the present scenario which needs to be addressed seriously and by all to prevent multi drug resistant tuberculosis.